REKOMENDASI PENERAPAN MANAJEMEN KARIR BERDASARKAN TALENTA PEGAWAI PT X - Mohammad Mizmara Alan Falihin (UNUSA Press, 2019)
Career management became a priority for improvement in X Company Employee surveys in 2014. Unfortunately, career planning has not been focused in human resource management. The study aimed to provide recommendations for employee planning and career development planning in the X Company. This descriptive research used cross sectional design. Data was taken through literature study, observation and document review. This study proves the importance of career management in the X Company. Career management is one element in the preparation of talent pool. Through good career management, it will have a positive impact for both the company and the individual itself. X Company is expected to conduct a more in-depth study on the formulation and implementation of career planning and development that will be implemented in the X Company and involves employees, human resource development, and organizations in the formulation and implementation.